Serum anti-PLA2R antibody and glomerular PLA2R deposition in Chinese patients with membranous nephropathy: A cross-sectional study. Issue 24 (June 2017) - Pang, Lu; Zhang, Ai-Min; Li, Hai-Xia; Du, Jia-Lin; Jiao, Li-Li; Duan, Nan; Liu, Yi; Yu, Dan
Abstract : Abstract: M-type phospholipase A2 receptor (PLA2R) is the major target antigen in primary membranous nephropathy (PMN). Previous studies have evaluated the diagnostic value of serum anti-PLA2R antibody. However, the correlation of serum anti-PLA2R antibody and glomerular PLA2R deposition, and their association with clinical characteristics need to be further evaluated. A total of 136 patients were involved as inception group because serum anti-PLA2R antibody and glomerular PLA2R antigen were simultaneously measured. We examined serum anti-PLA2R antibody by ELISA and glomerular PLA2R deposition by immunofluorescence assay. Positive serum anti-PLA2R antibody and glomerular PLA2R deposition were seen in 58.8% (80/136) and 95.6% (130/136) patients, respectively ( P  < .001). Proteinuria, serum total protein, serum albumin, serum creatinine, and estimated glomerular filtration rate (eGFR) had significant differences between patients with serum anti-PLA2R antibody and those without. Serum anti-PLA2R antibody levels were correlated with serum albumin, serum creatinine, eGFR, and proteinuria. Glomerular PLA2R deposition intensities were weakly correlated with proteinuria. Unexpectedly, there was a positive correlation rather than a negative correlation between glomerular PLA2R deposition intensity and eGFR. In conclusion, serum anti-PLA2R antibody is more closely correlated with disease activity and renal function than glomerular PLA2R deposition. Abstract : Supplemental Digital Content is available in the text